2023
DOI: 10.32479/ijeep.13999
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Energy Consumption, Foreign Direct Investment, and Labor Force Participation Using the VECM Model: Empirical Study in OECD Countries

Abstract: The purpose of this study is to determine the causal relationship as well as the long-term and short-term relationship between total energy consumption, foreign direct investment (FDI), and labor force participation rates in OECD countries from 1994 to 2019 using Granger Causality Test and Vector Error Correction Model (VCEM). In this study, it is found that energy consumption and FDI have a two-way causality, energy consumption and the labor force participation rate have a two-way causality and FDI and the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Conversely, Chen & Shao (2011) found that income has a positive impact on energy consumption, while capital and labour have a negative impact on energy consumption. Additionally, Wahyudi & Palupi (2023) found that energy consumption has been shown to contribute to higher economic growth in both developed and oil-exporting countries. Hu & Hu (2013) emphasized that labour has a positive impact on manufacturing production.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Conversely, Chen & Shao (2011) found that income has a positive impact on energy consumption, while capital and labour have a negative impact on energy consumption. Additionally, Wahyudi & Palupi (2023) found that energy consumption has been shown to contribute to higher economic growth in both developed and oil-exporting countries. Hu & Hu (2013) emphasized that labour has a positive impact on manufacturing production.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Foreign direct investment assists companies in other countries in improving productivity and expanding market reach. This is a crucial element that can determine the direction of economic policy, fostering economic development for society (Wahyudi & Palupi, 2023). In addition to Foreign Direct Investment (FDI), another macroeconomic variable that influences economic growth is international trade.…”
Section: Introductionmentioning
confidence: 99%
“…In various nations, international trade serves as a source of income and consistently contributes to GDP growth. International trade fosters progress within a country and naturally promotes technological advancements, transportation, industrialization, as well as the presence of foreign or multinational corporations, specialization, market expansion, and ultimately economic growth (Wahyudi & Palupi, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, individuals have the freedom to work, produce, consume, and invest according to their preferences, with the assurance of state protection and without hindrance from government actions. Several previous studies have indicated that there are several macroeconomic variables that can influence economic growth, namely foreign direct investment, international trade, labor force, inflation, and Pandemic Covid-19 (Adeniyi, 2020;Keho, 2017;Liang et al, 2021;Ma'in & Mat Isa, 2020;Nguyen et al, 2022;Pandya & Sisombat, 2017;Simanungkalit, 2020;Susilo, 2018;Wahyudi & Palupi, 2023). The neoclassical economic growth theory (Solow, 1956) and the endogenous growth theory (Romer, 1986) acknowledge the significance of innovation in stimulating growth, enhancing productivity, and fostering technological progress.…”
Section: Introductionmentioning
confidence: 99%
“…Foreign direct investment assists companies in other countries in improving productivity and expanding market reach. This is a crucial element that can determine the direction of economic policy, fostering economic development for society (Wahyudi & Palupi, 2023).…”
Section: Introductionmentioning
confidence: 99%